2019
DOI: 10.3390/ijerph16162850
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and Time-Based Walkability Index Design: A GIS-Based Proposal

Abstract: Encouraging people to walk as a means of transport throughout their daily lives has obvious benefits for the environment, the economy, and personal health. Specific features of the built environment have a significant influence on encouraging or discouraging walking. By identifying and quantifying these features we can design Walkability Indices (WI). The WI in the literature do not take factors related to comfort such as noise pollution and shade/sun conditions into account. Given the importance of these fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
3
16
0
6
Order By: Relevance
“…Hence, in the general condition, distance to amenities is perceived as a more critical indicator compared to urban greeneries for the comfort dimension. A similar result was also gained in the study of alShammas & Escobar (2019), where they also sent out a questionnaire to walkability experts to weigh different walkability factors. The study resulted in a 7.94 mean of importance for accessibility, and a 6.80 mean of importance for shading factor (greeneries)(al Shammas and Escobar, 2019).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Hence, in the general condition, distance to amenities is perceived as a more critical indicator compared to urban greeneries for the comfort dimension. A similar result was also gained in the study of alShammas & Escobar (2019), where they also sent out a questionnaire to walkability experts to weigh different walkability factors. The study resulted in a 7.94 mean of importance for accessibility, and a 6.80 mean of importance for shading factor (greeneries)(al Shammas and Escobar, 2019).…”
supporting
confidence: 56%
“…Although, it is needed to ensure that the optimum value of the incorporated indicator is known, which is one of the main reasons for including distance to amenities and urban greeneries for the comfort dimension. Other indicators that represent the comfort dimension have been used in other studies aside from the generative design approach, namely, noise, shading, street furniture, and building ratio (al Shammas and Escobar, 2019;Galal et al, 2020). However, there are no studies that have determined the optimum value of these indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Lucas revealed the incompleteness of Walk Score by observing the positive correlations between crime and Walk Score of 296 residential addresses in Rhode Island (Carr, Dunsiger et al, 2010). Tarek found that comfort factors can cause significant changes in walkability in the city of Madrid, measured at different times of the day and during different seasons (summer and winter) (Al Shammas and Escobar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Their longitudinal study in Perth, Australia, showed that walkability elements are not always equally important determinants of walking behavior [ 22 ]. The related indexes were weighted mainly through questionnaires [ 23 ] and expert scoring [ 24 ] in the related studies, where the hierarchical importance of the indexes was estimated according to the preferences of respondents and the professional knowledge of experts. However, both methods have subjective arbitrariness, and significant differences are found between the perspectives of experts and residents on the weight of factors in evaluating walking capacity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%